2019
DOI: 10.4103/jos.jos_13_19
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of salivary interleukin-1β (IL-1β), prostaglandin E2(PGE2) levels and pain intensity in children and adults during initial orthodontic treatment

Abstract: OBJECTIVES:To investigate pain intensity, interleukin-1β and prostaglandin E2 values in saliva during initial orthodontic treatment among varying age groups and their correlation between these mediators.MATERIALS AND METHODS:Twenty healthy patients distributed equally in age and gender groups were chosen. Unstimulated saliva was collected before the placement of orthodontic fixed appliance (T0), 1 hour after the placement of the appliance with 0.014” nickel titanium archwire (T1), 1 month after the first visit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
3
6
0
Order By: Relevance
“…Of particular interest, the IL-1β levels were significantly higher (+ 70%) in the test group with dentofacial deformities. It was previously demonstrated that the control patients displayed detectable salivary levels of IL-1β, and the orthodontic forces might drive an upregulation of this cytokine 14 , 30 , corroborating with the present investigation. The elevated IL-1β salivary levels in the test group might be attributed to the social context, or to the oral function disabilities that were observed in these patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Of particular interest, the IL-1β levels were significantly higher (+ 70%) in the test group with dentofacial deformities. It was previously demonstrated that the control patients displayed detectable salivary levels of IL-1β, and the orthodontic forces might drive an upregulation of this cytokine 14 , 30 , corroborating with the present investigation. The elevated IL-1β salivary levels in the test group might be attributed to the social context, or to the oral function disabilities that were observed in these patients.…”
Section: Discussionsupporting
confidence: 92%
“…This was because the patients in preparation for an orthognathic correction (considered here as the test group) were using an orthodontic device. This criterion was fundamental because orthodontic treatment has been previously correlated with salivary changes of inflammatory mediators, such as prostaglandin E2 and IL-1β 14 . Furthermore, the control group participants' sociodemographic features were similar to those seen in the test individuals undergoing OS, showing homogeneity of the study sample, regarding age, sex, BMI, educational level, ethnicity, and socioeconomic aspects, as well as the self-reported sleep quality, oral health status, and physical activity habits.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in line with those of other studies [4,6,19,20,22,23]. This can be understood in terms of the synthesis of various biochemical mediators (such as cytokines and prostaglandins) relative to hyperalgesia, with peaks occurring 24 h after applying force to the teeth [24,25]. Seven days after starting treatment, we observed that the level of pain decreased until reaching minimum values.…”
Section: Discussionsupporting
confidence: 92%
“…In addition to cytokines, OECs release soluble molecules that could potentially contribute to maintaining immune tolerance and tissue homeostasis. OECs express the enzymes cyclooxygenases (COXs) and indoleamine 2,3-dioxygenases (IDO), which are responsible for the synthesis of the immunomodulatory molecules PGE2 and kynurenines, respectively [64,65]. In fact, OECs secrete PGE2 and contribute to the maintenance of its concentration in saliva under physiological conditions (100 pg/mL) [65,66].…”
Section: Soluble Moleculesmentioning
confidence: 99%
“…OECs express the enzymes cyclooxygenases (COXs) and indoleamine 2,3-dioxygenases (IDO), which are responsible for the synthesis of the immunomodulatory molecules PGE2 and kynurenines, respectively [64,65]. In fact, OECs secrete PGE2 and contribute to the maintenance of its concentration in saliva under physiological conditions (100 pg/mL) [65,66]. PGE2 is the most abundant prostanoid in the human body, and its pro-inflammatory effect is well known.…”
Section: Soluble Moleculesmentioning
confidence: 99%